KDM5c Promotes Colon Cancer Cell Proliferation Through the FBXW7-c-Jun Regulatory Axis - Lin, Haishan; Ma, Nina; Zhao, Lei; Yang, Guowei; Cao, Bangwei (Frontiers in Oncology, 2020)
KDM5c is a histone demethylase that specifically demethylates trimethylated and dimethylated H3 Lys-4 to play a central role in transcriptional repression. C-Jun is a proto-oncogene and promotes cell proliferation when ectopically accumulated, but can be ubiquitinated by SCF (FBXW7), leading to its degradation. FBXW7 is an E3 ubiquitin ligase of c-Jun, and exhibits carcinostasis in colon cancer. Here, we report that overexpression of KDM5c in human colon cancer cells results in attenuated FBXW7 transcription and accumulated c-Jun protein, leading to increased proliferation of colon cancer cells. We show that overexpression of KDM5c can result in increased c-Jun protein levels and decreased ubiquitin levels, with no significant change in mRNA levels of c-Jun. KDM5c overexpression blocks the ubiquitin-proteasome proteolytic pathway of c-Jun by down-regulating the expression of FBXW7. KDM5c down-regulation of FBXW7 occurs by demethylation of H3K4me3 at TSS and downstream of the FBXW7 gene. And interaction of KDM5c with H3K4me3 downstream of FBXW7 gene may be followed by recruitment of DNMT3b to methylate the spatially close CpG island located near the FBXW7 TSS. This methylation represses FBXW7 gene expression, which can reduce c-Jun degradation via the ubiquitin-proteasome pathway. TCGA database analysis revealed high expression of KDM5c in colon cancer tissues. KDM5c expression in colon cancer was correlated with poor overall survival of patients in the first seven years. Data from TCGA showed that high expression of KDM5c was correlated with high DNA methylation of the FBXW7 gene, but was not positively correlated with methylation of the Jun gene. These results suggest that KDM5c regulation of colon cell proliferation is mainly mediated by the KDM5c-FBXW7-c-Jun axis.